PENERAPAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA JENJANG SEKOLAH MENENGAH PERTAMA (SMP) - Syamsul, Herawati (Idaarah: Jurnal Manajemen Pendidikan, 2017)
the success of an organization or institution is influenced by various factors, both factors coming from within and coming from the environment. Of these various factors, motivation is a factor that is dominant and can move other factors toward the effectiveness of work. In some instances, motivation is often equated with a car’s engine and steering wheel, which serves as a driving force and driver. The biggest source of motivation comes from the leader in this case is the principal. Principal leadership is an interrelated chain of aspects of teacher performance, pupils and all elements of the educational organization, so it is necessary to continuously improve in the form of self-development, insight so as to affect the progress of the school he leads.